Para onde vai o Brasil? Dilemas políticos e do modelo de desenvolvimento no cenário sul-americano - Jefferson O. Goulart (Centre de Recherches sur les Mondes Américains, 2019)
The impeachment of President Dilma Rousseff in Brazil signals the collapse of a cycle characterized by progressive governments in the South American subcontinent. This period had as its peculiarities the rise of popular leaders, democratic institutional stability, social inclusion policies and the strengthening of regional integration, both politically and economically. It was a time favored by the boom in commodity exports, which allowed many of these countries to adopt development policies abandoned in the previous cycle of neoliberal hegemony. The gifted hypothesis is that the deposition of the Workers' Party government reflects a regional movement for the rise of conservative ideas that is inseparable from the economic crisis and the definition of the development model of these countries.